KUKUM Artificial Marble - Kamarudin, Hussin, Brig. Gen. Dato' Prof. Dr. (Malaysian Invention and Design Society (MINDS), 2010)
Brig. Gen. Dato' Prof. Dr. Kamarudin Hussin and his team from School of Materials Engineering won silver for KUKUM Artificial Marble. ITEX 2005, 19th - 21st May 2005 was held at Putra World Trade Centre (PWTC), Kuala Lumpur.